Dynamic Economic Analysis from Difference Equation - Kumar, Nand Kishor (International Journal of Humanities, Education, and Social Sciences, 2025)
Dynamic economic analysis often involves understanding how economic variables evolve over time. One approach to modeling these dynamics is through the application of difference equations. Difference equations provide a framework for describing the evolution of economic variables in discrete time periods, making them particularly useful for analyzing time series data and economic processes that unfold in steps. In dynamic economic analysis, difference equations are an effective tool for modeling and comprehending how economic variables change with time. These difference equations are used by to study the behavior with economic systems and forecast future trends. Examples of these systems include market dynamics in the cobweb model and capital accumulation in the Solow growth model. Understanding the long-term behavior of complex systems is further aided by stability analysis, which guarantees that the models offer insightful information about economic processes. Stability analysis further aids in understanding the long-term behavior of these systems, ensuring that the models provide meaningful insights into economic processes.